2008
DOI: 10.1177/0743558407310721
|View full text |Cite
|
Sign up to set email alerts
|

Parents' and Sons' Perspectives on Video Game Play

Abstract: Public policy efforts to restrict children's access to electronic games with violent or sexual content are often predicated on assumptions about parental concerns. As an initial step in determining whether those assumptions are accurate, the authors conduct focus groups of 21 adolescent boys and 21 of their parents or guardians to explore parents' concerns, compare parents' and children's perceptions, and see whether these are consistent with the focus of proposed legislation and other public policy efforts. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 29 publications
2
53
0
1
Order By: Relevance
“…This in turn was related to heightened levels of aggressive behavior. Other research has found that adolescents who were "addicted" to video games showed a variety of psychosocial and health problems [5].Given these effects, it is not surprising that parents are most concerned with games interfering with schoolwork, social skills, and exercise [6]. Parents are also concerned with violent content in video games, but less so than the actual time spent by the adolescent in playing them.…”
mentioning
confidence: 97%
“…This in turn was related to heightened levels of aggressive behavior. Other research has found that adolescents who were "addicted" to video games showed a variety of psychosocial and health problems [5].Given these effects, it is not surprising that parents are most concerned with games interfering with schoolwork, social skills, and exercise [6]. Parents are also concerned with violent content in video games, but less so than the actual time spent by the adolescent in playing them.…”
mentioning
confidence: 97%
“…Studies in this area generally fall to two types: desirable and undesirable effects of video games [59]. Although understanding positive potentials of games, parents often concern about: 1) the balance between game playing and other activities, 2)game content, 3)possible negative impact of games, 4)mediation strategies [60].…”
Section: Common Factorsmentioning
confidence: 99%
“…Parents are also concerned that their children will withdraw from healthy social activities as a result of spending excessive time on video gaming [22,23]. Another concern is that children's academic grades will be compromised if they spend too much time playing video games [22]. Yet, some parents "sometimes used video games as a childcare management tool and reward, in hopes it would motivate the child to exhibit other positive behaviors" [2, p.123].…”
Section: Relevance Of Vgrs In the Evolving Video Game Spacementioning
confidence: 99%
“…Parents are mainly concerned that prolonged video gaming could result in displacement of time intended for homework or studies [2,21,22,23]. Parents are also concerned that their children will withdraw from healthy social activities as a result of spending excessive time on video gaming [22,23]. Another concern is that children's academic grades will be compromised if they spend too much time playing video games [22].…”
Section: Relevance Of Vgrs In the Evolving Video Game Spacementioning
confidence: 99%
See 1 more Smart Citation